2021
DOI: 10.1016/j.jbc.2021.100909
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of substrate specificity in human cytidine deaminase family APOBEC3s

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 81 publications
(131 reference statements)
2
17
0
Order By: Relevance
“…While small molecule inhibitor development has not been successful, modified ssDNA oligonucleotides with the C 0 changed to 2′-deoxy-zebularine or 2′-deoxy-zebularine analogs have been shown to inhibit A3s 27, 28 although not with high potency. Zebularine was initially identified as a cytidine deaminase (CDA) inhibitor; however, CDA inhibitors do not inhibit A3s because, unlike CDAs that modify the single nucleoside, A3s deaminate cytidine in context of ssDNA 47 , suggesting they may require additional features beyond those needed for CDA binding. The high resolution (1.5 Å) A3G-CTD2:dZ-ssDNA structure we present here now helps understand both similarities between CDAs and A3s and the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…While small molecule inhibitor development has not been successful, modified ssDNA oligonucleotides with the C 0 changed to 2′-deoxy-zebularine or 2′-deoxy-zebularine analogs have been shown to inhibit A3s 27, 28 although not with high potency. Zebularine was initially identified as a cytidine deaminase (CDA) inhibitor; however, CDA inhibitors do not inhibit A3s because, unlike CDAs that modify the single nucleoside, A3s deaminate cytidine in context of ssDNA 47 , suggesting they may require additional features beyond those needed for CDA binding. The high resolution (1.5 Å) A3G-CTD2:dZ-ssDNA structure we present here now helps understand both similarities between CDAs and A3s and the observed differences.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the enhancement of APOBEC3A expression by pro-inflammatory factors, including IFNα, IFNγ, or LPs, has also been described [ 26 , 27 ]. Interestingly, it has been observed that APOBEC3A and APOBEC3B cytidine deaminases are the two members of this family of proteins that are the most frequently overexpressed in many types of malignancies [ 28 ]. Notably, some studies have revealed that APOBEC3A exhibits the highest enzymatic activity compared to other family components [ 7 ], suggesting the special importance of this molecule in cancer biology.…”
Section: Deaminases and Cancer Inflammationmentioning
confidence: 99%
“…Regarding this idea, it has been observed that the APOBEC-mediated deamination preferentially occurs in TCW-specific DNA sequence motifs (“W” being any type of nucleotide) [ 80 ]. Furthermore, structural studies revealed substrate specificity differences between distinct members of the APOBEC3 group, such as APOBEC3A, 3B, or 3G [ 28 ], showing the existence of deamination motif heterogeneity regarding each deaminase. Therefore, an in-depth analysis of solid tumour biopsies could be proposed to establish a correlation between the activity of specific deaminases and the most probable mutational genome map.…”
Section: Diagnostic and Therapeutic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of double-domain enzymes, only the C-terminal domain is catalytically active; the N-terminal domain is similar to the catalytic domain in structure, but not in function, and is often referred to as 'pseudocatalytic ' [14]. A3 enzymes require a minimum 5-mer oligonucleotide for binding [15], where the ssDNA adopts a conformation that allows the target cytosine to access the active site (Figure 1C) [16][17][18][19]. Most A3 enzymes have a 5′-TC-3′ dinucleotide sequence preference [20][21][22][23][24][25][26]; A3G is the exception and prefers to deaminate cytosine in a 5′-CC-3′ motif [27][28][29].There is a large degree of sequence and structural conservation within and across the three Z-domains, but some unique features between the protein family members may be exploited to achieve selectivity during inhibitor development.…”
mentioning
confidence: 99%